2016
DOI: 10.1021/acs.est.5b06367
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Chemistry and Morning Isoprene Can Drive Urban Ozone Downwind of a Major Deciduous Forest

Abstract: Isoprene is the predominant non-methane volatile organic compound emitted to the atmosphere and shapes tropospheric composition and biogeochemistry through its effects on ozone, other oxidants, aerosols, and the nitrogen cycle. Isoprene is emitted naturally by vegetation during daytime, when its photo-oxidation is rapid, and in the presence of nitrogen oxides (NOx) produces ozone and degrades air quality in polluted regions. Here, we show for a city downwind of an isoprene-emitting forest (St. Louis, MO) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…CC-BY 3.0 License. and box model simulations (Millet et al, 2016). This impact can be further complicated by uncertainty in emissions of BVOC and model resolutions.…”
Section: Influence On Reactive Nitrogen and Ozonementioning
confidence: 99%
See 2 more Smart Citations
“…CC-BY 3.0 License. and box model simulations (Millet et al, 2016). This impact can be further complicated by uncertainty in emissions of BVOC and model resolutions.…”
Section: Influence On Reactive Nitrogen and Ozonementioning
confidence: 99%
“…This impact can be further complicated by uncertainty in emissions of BVOC and model resolutions. For example, a recent study by Millet et al (2016) shows that in a city downwind of an isoprene-rich forest, daytime O 3 can be largely modulated by the chemical removal of isoprene throughout the night. Such local scale event may only be captured by a very high resolution model with detailed characterization 5 of emission sources.…”
Section: Influence On Reactive Nitrogen and Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…In moderately polluted environments, e.g. forests surrounding urban areas, nitrate radicals (NO 3 ), which form mainly from the oxidation of NO 2 by O 3 , are the dominant oxidant of isoprene at night when photochemical production of OH has diminished (Ng et al, 2017). The nitrate radicals can be abundant at night and short-lived during the day due to their rapid photolysis in sunlight and its reaction with NO (Wayne et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This region is downwind from the urban area of Sydney, where the largest emission source of NO x and VOC precursors is motor vehicles, and hence, causes elevated ozone downwind in the South West of Sydney. Various studies have shown that areas downwind from the upwind emission of precursors experience high ozone [32,33].…”
Section: Discussionmentioning
confidence: 99%